2020
DOI: 10.1038/s41372-019-0578-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of extubation success using noninvasive positive pressure ventilation (NIPPV) versus noninvasive neurally adjusted ventilatory assist (NI-NAVA)

Abstract: Objective Compare rates of initial extubation success in preterm infants extubated to NIPPV or NI-NAVA. Study design In this pilot study, we randomized 30 mechanically ventilated preterm infants at the time of initial elective extubation to NI-NAVA or NIPPV in a 1:1 assignment. Primary study outcome was initial extubation success. Results Rates of continuous extubation for 120 h were 92% in the NI-NAVA group and 69% in the NIPPV group (12/13 vs. 9/13, respectively, p = 0.14). Infants extubated to NI-NAVA remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…In premature infants synchronized NIPPV was associated with greater decrease in the work of breathing (WOB) than nCPAP alone 13 . NIV-NAVA proved more efficacious than both non-synchronized NIPPV and nCPAP after extubation 14 , 15 . The combination of heliox and NIV-NAVA may promote NIV success, providing a synergistic approach to premature infants with respiratory failure.…”
Section: Introductionmentioning
confidence: 94%
“…In premature infants synchronized NIPPV was associated with greater decrease in the work of breathing (WOB) than nCPAP alone 13 . NIV-NAVA proved more efficacious than both non-synchronized NIPPV and nCPAP after extubation 14 , 15 . The combination of heliox and NIV-NAVA may promote NIV success, providing a synergistic approach to premature infants with respiratory failure.…”
Section: Introductionmentioning
confidence: 94%
“…A decreased neural respiratory effort was observed during NIV-NAVA and NIPPV when compared to NCPAP. The higher MAP provided during NIPPV (median = 8.2) and NIV-NAVA (median = 9.3) proportionally offloaded the diaphragm, taking some of the work of breathing away from the infant as previously described 8,12,26 . Interestingly, the NIPPV mode on the Servo-i ventilator has flow-synchronization using an internal sensor, which this study has demonstrated to be largely ineffective.…”
Section: Diaphragmatic Activitymentioning
confidence: 68%
“…The apnea detection time used to trigger backup ventilation was of 10s and a shorter period may have been more appropriate in these patients 35 . While some small randomized controlled trials 8,36 and retrospective studies [37][38][39] reported reduced respiratory failure rates with NIV-NAVA, there is a lack of good evidence to determine its superiority over other modes of noninvasive support 40 . Thus, until larger randomized trials are conducted, some caution should be exercised when integrating NIV-NAVA into the care of extremely preterm infants.…”
Section: Respiratory Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons underpinning our success may be found in the evidence base for each individual intervention we adopted in our “BPD Prevention Bundle of Interventions” and “No BPD Roadmap.” The postnatal interventions of varying degrees of evidence supporting efficacy in preventing BPD included high-frequency ventilation 24 ; volume-targeted ventilation 25 ; surfactant therapy 26 , 27 ; CPAP use 15 , 25 , 28 , 29 , 30 , 31 ; administration of caffeine 32 , 33 , 34 , 35 ; vitamin A 36 , 37 , 38 ; azithromycin 39 ; human breast milk 40 ; and inhaled or systemic steroids 41 , 42 , 43 , 44 , 45 ; and lowered oxygen saturation targets of 85% to 95% up to 34 weeks’ gestation. 46 , 47 The interventions that we adopted that improved various aspects of short-term respiratory function, although they have not yet been shown to decrease BPD, included the use of extended CPAP, 48 neurally adjusted ventilatory assist, 25 , 28 , 29 , 30 , 40 high-flow nasal cannula, 49 , 50 , 51 , 52 and inhaled β-agonists. 53 Permissive hypercarbia and the use of diuretics were not encouraged in our bundle.…”
Section: Discussionmentioning
confidence: 99%